Implementing the Inclusive Education Policy in Three RAK Primary Government Schools: An Investigation study - Al Shehhi, Khawla (2016)
In recent years, many efforts have been developed to apply the latest methods in the special education field. One of these methods is including special needs students with non-special needs peers in regular schools. Ratifying the UN Convention on the Rights of Persons with Disabilities, the UAE issued the Federal Law No. 14/2009, amending Law No. 29/2006, to ensure that all individuals with special needs have access to education in mainstream or special classrooms (Ministry of Social Affairs 2006). This study aims to investigate the implementation of Inclusive Education policy in three RAK primary government schools (from Grade one to Grade five). Mixed methods of qualitative and quantitative approaches were used in this study; semi-structured interviews, questionnaires and observations. The study sample consisted of six students with a different disability, their parents, school principals, special education specialists and teachers from selected schools. The results indicate that there seems to be a “Masked Inclusion” where all schools do welcome these students but there is little care for their education, and there is a lack of communication between them and the Educational Zone. Based on these results, this study provides a set of recommendations for a better implementation for The Ministry of Education, RAK Educational Zone and schools. This is to overcome some of the challenges faced in the field that would provide better opportunities for the implementation process of inclusion to succeed.